Discourses of men's suicide notes a qualitative analysis - Galasiński, Dariusz 1964- (Bloomsbury advances in critical discourse studies, 2017)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Dedication -- Contents -- Acknowledgements -- 1 Introduction -- Aims of the book -- The book's projects -- Suicide notes -- The suicidal mind -- Analyses of contents -- Suicide notes as social texts -- Masculinity -- Fatherhood -- Masculinity and suicide -- Discourse analysis -- Qualitative suicidology -- Data -- Vocabulary -- Book overview -- Appendix -- 2 The Gift of Suicide: Stories of the Ultimate Solution -- The gift -- The giver -- The addressee -- Relationships -- Conclusions -- Appendix -- 3 Ambiguities of Suicide: Stories of the Reasons -- Stories of the generalities -- Internal rationality -- Blame -- Conclusions -- Appendix -- 4 Suicide: The Act Outside of Discourse -- Distancing -- It -- Suicide directly? -- Men's decisions and apologies -- Conclusions -- Appendix -- 5 Men Who Kill Themselves: Identities in Suicide Notes -- Gender identity -- Men don't kill themselves -- Fatherhood -- Men's fears -- Conclusions -- Appendix -- 6 The Note: Exercise in Timing -- A special farewell -- Neat handwriting -- Timing in the notes -- Present perspective -- The future -- Conclusions -- Appendix -- 7 See You Later: Non-finality of Suicide -- A goodbye? -- Love and life -- Life continues -- Failed attempt? -- Certainty -- Conclusions -- Appendix -- 8 Instructions: Narratives of Continuing Control -- Positioning theory -- Directives -- Bring me flowers -- Don't slouch! -- Minutiae -- Conclusions -- Appendix -- 9 Conclusions: Dilemmas of Suicide -- Three paradoxes -- Suicide notes -- The lived perspective -- The final project -- The final word -- Appendix -- Notes -- Bibliography -- Index